Numerical simulation of salt transport and crystallization in drying Prague sandstone using an experimentally consistent multiphase model. (October 2017) - Grementieri, L.; Molari, L.; Derluyn, H.; Desarnaud, J.; Cnudde, V.; Shahidzadeh, N.; de Miranda, S.
Abstract: Drying of porous media in the presence of salt is a very common phenomenon with many applications but it is not totally understood so far. Some experiments that recently appeared in the literature have shown that the kinetics of drying not only strongly depends upon the quantity of precipitated salt but also upon the form in which the salt precipitates. In this paper, a coupled multiphase model that is capable of describing the different drying kinetics taking into account the different efflorescence formations is presented. The model is then validated through two different experimental campaigns on drying in presence of NaCl solution. Highlights: A new multiphase model for the simulation of salt transport and salt crystallization in drying porous media is proposed. The model is able to take into account the different type of efflorescence due to the different environmental conditions. The model is validated through laboratory tests on Prague sandstone. The tests are performed with traditional and very innovative techniques. The results of the model confirm the interpretation that the different drying kinetics are due to the type of efflorescence formed.